Impact of Fuel Type on the Internal Combustion Engine Condition - Schauperl, Zdravko; Nikšić, Mladen; Kolednjak, Davor (Promet - Traffic&Transportation, 2012)
The paper studies the influence of liquefied petroleum gas as alternative fuel on the condition of the internal combustion engine. The traffic, energy, economic and ecological influence as well as the types of fuel are studied and analyzed in an unbiased manner, objectively, and in detail, and the obtained results are compared with the condition of the engine of a vehicle powered by the stipulated fuel, petrol Eurosuper 95. The study was carried out on two identical passenger cars with one being fitted with gas installation. The obtained results show that properly installed gas installations in vehicles and the usage of LPG have no significant influence on the driving performances, but they affect significantly the ecological and economic parameters of using passenger cars.